RELAKSASI NAFAS DALAM MENGGUNAKAN AROMATERAPI MAWAR TERHADAP KECEMASAN IBU HAMIL TRIMESTER 3 DALAM MENGHADAPI PERSALINAN - Pardede, Nurhayati; Lestari Nurul Aulia, Devy (Universitas Batam, 2025)
According to WHO data in 2016, around 10% of women experienced anxiety during pregnancy and 13% of women experienced anxiety after giving birth. The risk level for anxiety disorders in pregnant women in developing countries is around 15.6% and in Indonesia there are around 28.7% of pregnant women in their third trimester who experience anxiety. The deep breathing relaxation technique is a technique for taking deep breaths, slow breathing (holding inspiration to the maximum) and exhaling slowly. This study aims to determine the effect of breath relaxation using rose aromatherapy on the anxiety of pregnant women in the third trimester when facing childbirth. Pre-experimental research method with a one group pre test and post test design approach. This research was conducted at the Meral Community Health Center in February - August 2024 on 44 pregnant women in the third trimester. The data was analyzed using SPSS. The research results showed that the average anxiety before deep breath relaxation using rose aromatherapy was 18.48 and the average after was 8.75. Data analysis obtained p-value 0.001 (p<0.05). So it can be concluded that there is an effect of breath relaxation using rose aromatherapy on the anxiety of pregnant women in the third trimester when facing childbirth. It is hoped that pregnant women can further practice deep breathing relaxation techniques to reduce anxiety. Keywords: Deep breathing relaxation, rose aromatherapy, anxiety, pregnant women, 3rd trimester